2001
DOI: 10.1002/pits.1025
|View full text |Cite
|
Sign up to set email alerts
|

Designing effective interventions for children at‐risk for antisocial behavior: An integrated model of components necessary for making valid inferences

Abstract: Children demonstrating antisocial behavior patterns are at-risk for a host of negative outcomes including school failure, peer and teacher rejection, academic difficulties, and future delinquency. These children are undoubtedly in need of effective and appropriate interventions to address problem areas in both behavioral and academic domains. To ensure that academic and sociobehavioral interventions will be more successful, three main components: (a) social validity, (b) treatment integrity, and (c) generaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 51 publications
1
22
0
2
Order By: Relevance
“…Lane, Beebe-Frankenberger, Lambros, and Pierson (2001) reported that interventions utilising self-monitoring records or a task analysis checklist improve treatment integrity. Feedback from facilitators is also provided via fortnightly supervision sessions, where implementation issues, process issues, and practical guidelines to overcome difficulties are discussed.…”
Section: Intervention Programmentioning
confidence: 99%
“…Lane, Beebe-Frankenberger, Lambros, and Pierson (2001) reported that interventions utilising self-monitoring records or a task analysis checklist improve treatment integrity. Feedback from facilitators is also provided via fortnightly supervision sessions, where implementation issues, process issues, and practical guidelines to overcome difficulties are discussed.…”
Section: Intervention Programmentioning
confidence: 99%
“…Research on treatment integrity has identified substantial variability in selfreport and direct observation methods (Lane, Beebe-Frankenberger, Lambros, & Pierson, 2001;Roe & Vukelich, 2001). Within the context of a complex intervention, there are strengths and limitations of either approach.…”
Section: Classroom Assessmentsmentioning
confidence: 99%
“…(...)" (Reforma do Direito de Menores, 1999, pp. 300-305). identificados, nomeadamente, o uso de drogas, uma história familiar de comportamentos de alto-risco, a falência da supervisão parental, expectativas parentais negativas em relação ao adolescente, castigos inconsistentes ou excessivamente severos, conflitos familiares, violência doméstica, a falta de investimento escolar, o insucesso escolar, a imaturidade emocional (baixo auto-controlo, agressividade e impulsividade), os pares anti-sociais e os comportamentos disruptivos com início na infância (e.g., Bender & Losel, 1997;Born, Chevalier, & Humblet, 1997;Lane, Beebe-Frankenberger, Lambros, & Pierson, 2001).…”
Section: Introductionunclassified